Project International School Cidade Viva: Performance Management by Competence - Bezerra Neto, Francisco das Chagas (2021)
The present article aims to analyze the management process of the collaborators of ths Internacional School Cidade Viva, followed by the proposal to implement the Performance Management by Competence model. In this perspective, the present study, through exploratory research, of qualitative nature, deductive method bibliographic data collection, developed in order to point out the tools of this model and its results so that they can provide performance improvement and increase the level of satisfaction of its collaborators. It should be noted that the International School Cidade Viva is a Third Sector institution, therefore, not for profit. Furthermore, it should be noted that their main mission is to promote the integral education of leaders, so that they are able to serve for God and for the neighbor with excellence and to transform the world through Christian ethics. Finally, in view of the proposed objectives, it was sought to outline mechanisms capable of measuring the professional performance of the collaborators. relating it to the ideal competencies for the exercise of its position / function and for the fulfillment of the organizational objectives, in order to identify performance potentials and weaknesses.